Research on High School English Reading Instruction with a Focus on Deep Learning - Zheng, Mengwei (Journal of Educational Research and Policies, 2026)
Deep learning in teaching is a meaningful learning process in which students are the center of the classroom, fully engaged and participating in learning activities, thus achieving healthy development. Focusing on deep learning in English instruction helps to break away from fragmented language teaching, guiding students to explore the deeper meanings of texts and to establish correct emotional attitudes and values towards society, themselves, and nature. This paper aims to explore, using the high school reading lesson “The Stone in the Road” as an example, how to practice the principle of fostering integrity and promoting rounded development in high school English classrooms through a focus on deep learning, and to propose corresponding recommendations.